2020
DOI: 10.3390/biomedicines8090295
|View full text |Cite
|
Sign up to set email alerts
|

The Biomedical Uses of Inositols: A Nutraceutical Approach to Metabolic Dysfunction in Aging and Neurodegenerative Diseases

Abstract: Inositols are sugar-like compounds that are widely distributed in nature and are a part of membrane molecules, participating as second messengers in several cell-signaling processes. Isolation and characterization of inositol phosphoglycans containing myo- or d-chiro-inositol have been milestones for understanding the physiological regulation of insulin signaling. Other functions of inositols have been derived from the existence of multiple stereoisomers, which may confer antioxidant properties. In the brain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 243 publications
(317 reference statements)
1
46
0
Order By: Relevance
“…Over the last decade, experimental studies, calcium metabolism, and dysregulation of neuronal calcium signalling and alterations in the expression of calcium signalling proteins have been observed in animal models of familial Alzheimer’s disease (AD) [ 43 , 44 , 45 ] and this a possibility of correcting neuronal calcium disruption as a therapeutic approach for AD [ 45 ]. There be could be a role of leptins in osteoporosis [ 46 ], inositols [ 47 ], or Calmodulin [ 48 ] for delaying cognitive impairment, but this needs further research. The current recommendation suggests calcium and vitamin D supplementation in those receiving treatment for osteoporosis and for care home residents who are at high risk of calcium and vitamin D insufficiency [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, experimental studies, calcium metabolism, and dysregulation of neuronal calcium signalling and alterations in the expression of calcium signalling proteins have been observed in animal models of familial Alzheimer’s disease (AD) [ 43 , 44 , 45 ] and this a possibility of correcting neuronal calcium disruption as a therapeutic approach for AD [ 45 ]. There be could be a role of leptins in osteoporosis [ 46 ], inositols [ 47 ], or Calmodulin [ 48 ] for delaying cognitive impairment, but this needs further research. The current recommendation suggests calcium and vitamin D supplementation in those receiving treatment for osteoporosis and for care home residents who are at high risk of calcium and vitamin D insufficiency [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present results establish a role of the juxtamembrane region of APP containing the CBS as a regulator of the size of Aβ peptides produced by processing of APP processing: this specific region could then be a novel target for inhibiting cholesterol-binding and reducing the production of toxic Aβ species. K28 has been targeted using lysine-specific molecular tweezers to inhibit assembly and toxicity of amyloid peptides (5860). It will be of interest to determine whether editing of this residue using CRISPR Cas9, antisense knockdown of the mutant protein, or treatment with antibodies targeting the juxta-membrane region will alter APP processing.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that an antioxidant therapy has beneficial effects in vivo and in vitro animal models for MS. In the context of antioxidant therapy, due to their own antioxidant properties, the use of nutraceutics in neurodegenerative, inflammatory, and metabolic diseases is in constant expansion in order to ameliorate or prevent aging-related diseases [ 113 ]. These molecules are easily extracted from plants or derived from fermentation in bioreactors [ 113 ].…”
Section: The Camp Signalling In the Regulation Of Mitochondrial Acmentioning
confidence: 99%
“…In the context of antioxidant therapy, due to their own antioxidant properties, the use of nutraceutics in neurodegenerative, inflammatory, and metabolic diseases is in constant expansion in order to ameliorate or prevent aging-related diseases [ 113 ]. These molecules are easily extracted from plants or derived from fermentation in bioreactors [ 113 ]. Among people with MS, nutraceutics are commonly used, often concomitantly with conventional treatment [ 114 ].…”
Section: The Camp Signalling In the Regulation Of Mitochondrial Acmentioning
confidence: 99%
See 1 more Smart Citation